Time to get tough : making America #1 again - Trump, Donald, 1946- (Washington, D.C. : Regnery Pub., 2011)
With his trademark candor and charisma, Trump reveals his hard-line, commonsense solutions to the problems plaguing us today and shows how we can put our country back on the path to greatness.
Get tough -- Take the oil -- Tax China to save American jobs -- It's your money, you should keep more of it -- A government we can afford -- Strengthen American muscle -- A safety net, not a hammock -- Repeal Obamacare -- It's called illegal immigration for a reason -- The America our children deserve -- The press and the presidency.
Updated for 2016
Includes bibliographical references (pages 193-207) and index.
Keywords: Since 2009; Economic history; Economic policy; Politics and government; Economic policy -- United States; United States -- Economic policy -- 2009-; United States -- Economic conditions -- 2009-; United States -- Politics and government -- 2009-; United States; United States -- Economic conditions; United States -- Politics and government